The Effect of LiBOB Addition on Solid Polymer Electrolyte (SPE) Production based PVDF-HFP/TiO2/LiTFSI on Ionic Conductivity for Lithium-Ion Battery Applications - Titik Lestariningsih; Qolby Sabrina; Christin Rina Ratri; Achmad Subhan; Slamet Priyono (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2022)
SPE (Solid Polymer Electrolyte) is an alternative to substitute conventional liquid electrolytes as it has a better safety level and has been produced using the solution casting method. An effort to increase the SPE conductivity of the PVDF-HFP/TiO2/ LiTFSI system has been carried out by adding LiBOB as an additive. LiBOB (lithium bis(oxalate) borate) is a salt compound that can interfere with the crystallization process of polymer chains, so it is expected to increase ion conductivity. However, the results showed a decrease in the conductivity from 3.643 x 10-5 S/cm to 8.658 x 10-6 S/cm. These results were proven by the XRD, FTIR, SEM, and TGA characterization. Based on XRD (X-ray Diffraction) analysis, the addition of LiBOB increased the crystallinity phase. The results of the SEM (Scanning Electron Microscope) analysis showed that the pore size was partially reduced, the distance between the pores became longer, and the pore closure occurred due to agglomeration. The FTIR (Fourier Transform Infrared spectroscopy) analysis showed the interaction of LiBOB salts in the PVDF-HFP/LiTFSI/TiO2 system, and based on TGA (Thermogravimetric Analysis) analysis, the addition of LiBOB affected the heat stability of the SPE. The CV (Cyclic Voltammetry) analysis showed that the addition of LiBOB in the SPE system could reduce the reversibility and magnitude of the current.